2018
DOI: 10.15171/ehem.2018.05
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical waste disposal systems of health facilities in Ethiopia

Abstract: Background: Biomedical waste generated from health and health-related activities can be grouped as general waste and hazardous waste. This remains true if and only if there is proper on-site handling, such as the segregation and separation of waste based on the type and nature of the source. Methods: A stratified random sampling design was used to provide representative results for Ethiopia, for various types of facility and management authorities, and for each of the 11 regions. Totally, 1327 health facilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2121
2121

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…are the major risks and hazards of poorly managed HCW [2, 3]. Hence, management of healthcare wastes requires special attention and needs to be assigned high priority [46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…are the major risks and hazards of poorly managed HCW [2, 3]. Hence, management of healthcare wastes requires special attention and needs to be assigned high priority [46].…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, as in many developing countries, compliance with the recommended HCW segregation practice still not jumped from paper [4, 6, 16]. Moreover, safe HCWM has been given very little attention and many facilities do not meet the minimum standards required for proper handling of HCWs [7, 16].…”
Section: Introductionmentioning
confidence: 99%
“…ealthcare waste is the total waste stream that, regardless of its volume, characteristics, and composition, is produced from health centers, health research centers, and laboratories, hospitals, clinics, medical research centers, drug factories, pharmacies, etc. [1]. These wastes account for around 1%-2% of urban wastes.…”
Section: Introductionmentioning
confidence: 99%
“…Although 75% to 90% of the healthcare waste generated is non-toxic, the remaining 10%-25% is considered "hazardous" [6,7]. The results of a cross-sectional study in selected Addis Ababa hospitals showed that the average waste production rate varies between 0.361 and 0.669 kg/patient/d and consists of 58.69% and 41.31% of non-hazardous and hazardous waste, respectively [1].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare waste (HCW) can be defined as the total waste that is generated from healthcare establishments, health-related research facilities, and laboratories. Hospitals, clinics, laboratories, medical research centers, pharmaceutical manufacturing plants, pharmacies, blood banks, veterinary health care centers, and home healthcare activities are some of the generators of healthcare waste irrespective of volumes, characteristics, and composition (Derso et al, 2018). HCW mismanagement may expose people inside the healthcare facilities (e.g.…”
Section: Introductionmentioning
confidence: 99%